Extending the Dialogue: Responding to Indonesian Multicultural Children’s Literature Cap Go Meh - Durriyah, Tati Lathipatud; Dewayani, Sofie (Universitas Sanata Dharma, 2024)
Cap Go Meh is an Indonesian picture book with interreligious and multiethnic themes and has been translated to English and been awarded for promoting multiculturalism. Studies that focus on reader response to interreligious theme of children’s literature are scarce. This study examines a reading engagement of a group of Muslim preservice to Cap Go Meh read aloud. Using a framework of reader response theory that pays attention to cultural influences including religions, this qualitative study posed a question: How do Indonesian Muslim preservice teachers respond to the multicultural story in Cap Go Meh. The respondents’ writing responses generated two major themes. One was concerned with how the preservice teachers relate to Cap Go Meh and how its narrative leads to their reflections about diversity. The other one focused on how the participants might extend the story of Cap Go Meh and highlighted the preservice teachers’ concerns with the role of adults (parents) in the story. Additional data from one participant could potentially show a case for furthering literary experiences using multicultural children’s literature. The researchers note that responses to sensitive issues such as religious diversity occur mostly in a context where there is encouragement from teachers. In this case, it is crucial to highlight the importance of bringing multicultural children’s literature like Cap Go Meh as a medium to discuss the lives and perspective of others.